Risk behaviours of illicit drug users while travelling - Tatja Kostnapfel Rihtar; Igor Švab (Zdravniški Vestnik, 2013)
Introduction: Despite various formal limitations, an increasing number of opioid users, especially those stabilised in substitution therapy, travel abroad, away from their permanent residence to neighbouring and remote countries on other continents. Drug users are particularly at risk to get infected with hepatitis A, B, C and HIV during travelling.The main objectives of the study were to identify and determine the frequency of potential travel-related risk behaviour, such as illicit drug use, sharing of injecting equipment, unprotected sex, involvement in criminal activities and the extent of risk in illicit drug users, included in the programmes of the Centers for Prevention and Treatment of Drug Addiction in Slovenia. Methods: The study was carried out in two phases. The first phase included semi-structured interviews conducted in a group of drug users willing to participate in the study. Based on the analysis of transcripts and additional data, the original questionnaire Risky behaviour of illicit drug users during travels was developed and filled in anonymously and on a voluntary basis at the network of Centres for Prevention and Treatment of Drug Addiction. Univariate analysis between independent and dependent factors was conducted based on chi-square test and t-test for independent factors. Multivariate analysis of the impact of independent factors on the dependent factor was conducted based on binary logistic regression. Results: The questionnaire was filled out anonymously and voluntarily by 776 individuals in 14 Slovene centres for prevention and treatment of drug addiction. The results confirmed the first hypothesis that drug users travelling away from their permanent residence are more likely to share their injecting equipment, and engage in unprotected sex and in drug-related crime, and the second hypothesis stating that illegal drug users included in the substitution treatment programmes, who regularly use drugs at home, more often use drugs while travelling than individuals included in the substitution treatment programmes, who never use drugs at home. The hypothesis that illegal drug users who travel abroad more often stop their substitution therapy than those who stay at home was not proven true. Conclusion: The results of quantitative analysis showed a low prevalence of travel-related risk behaviours, including the sharing of injecting equipment, and engaging in unprotected sex and drug-related crime.